2015
DOI: 10.4141/cjss-2014-076
|View full text |Cite
|
Sign up to set email alerts
|

Upscaling modelled crop yields to regional scale: A case study using DSSAT for spring wheat on the Canadian prairies

Abstract: . 2015. Upscaling modelled crop yields to regional scale: A case study using DSSAT for spring wheat on the Canadian prairies. Can. J. Soil Sci. 95: 49Á61. Dynamic crop models are often operated at the plot or field scale. Upscaling is necessary when the process-based crop models are used for regional applications, such as forecasting regional crop yields and assessing climate change impacts on regional crop productivity. Dynamic crop models often require detailed input data for climate, soil and crop managemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 43 publications
(41 reference statements)
0
10
0
Order By: Relevance
“…For wheat, the AgMIP (Agricultural Model Intercomparison and Improvement Project) listed 27 representative wheat models around the world (Asseng et al, 2013). The decision support system for agrotechnology transfer (DSSAT) including the CERES-Wheat model has been widely used over the last 25 years by many researchers for many different applications, and it has been shown to be capable of robust yield predictions across various environmental, soil, and management strategy conditions (Landau et al, 1998;Jones et al, 2003;Nain et al, 2004;Fang et al, 2008;Thorp et al, 2010;Liu et al, 2011;Huffman et al, 2015). When applied over a large-scale area, however, the model has shown low prediction performance because the boundary conditions (soil, management) are often poorly known and model parameters are uncertain (Moulin et al, 1998;Dorigo et al, 2007).…”
Section: Introductionmentioning
confidence: 98%
“…For wheat, the AgMIP (Agricultural Model Intercomparison and Improvement Project) listed 27 representative wheat models around the world (Asseng et al, 2013). The decision support system for agrotechnology transfer (DSSAT) including the CERES-Wheat model has been widely used over the last 25 years by many researchers for many different applications, and it has been shown to be capable of robust yield predictions across various environmental, soil, and management strategy conditions (Landau et al, 1998;Jones et al, 2003;Nain et al, 2004;Fang et al, 2008;Thorp et al, 2010;Liu et al, 2011;Huffman et al, 2015). When applied over a large-scale area, however, the model has shown low prediction performance because the boundary conditions (soil, management) are often poorly known and model parameters are uncertain (Moulin et al, 1998;Dorigo et al, 2007).…”
Section: Introductionmentioning
confidence: 98%
“…Its cultivar coefficients used in DSSAT v4.0 were determined by Wang et al (). A recent study (Huffman et al , ) showed that spring wheat yields aggregated from the DSSAT simulations with AC Barrie on different soils reasonably matched reported spring wheat yields at the census agricultural region level on the Canadian Prairies.…”
Section: Methodsmentioning
confidence: 81%
“…The soil properties from the 1998 to 2001 experiments in Ottawa were used to simulate the site yield. Soil data for the ecodistrict were obtained from the Canadian Soil Information System (CanSIS) (MacDonald & Kloosterman 1984) and Soil Landscapes of Canada (SLC), version 3.2 (Soil Landscapes of Canada Working Group 2010), as described in Huffman et al (2015). A total of 19 types of soils were retrieved from CanSIS for the selected ecodistrict.…”
Section: Methodsmentioning
confidence: 99%